2005
DOI: 10.1295/polymj.37.489
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Thermal Behavior of Poly(o-anisidine)/Poly(ethylene terephthalate) Composite

Abstract: ABSTRACT:Poly(o-anisidine)-Poly(ethylene terephthalate) composite film was prepared by chemical oxidative polymerization method. The composite film shows a conductivity of about 15.6 K À1 cm À1 with 3.5 wt. % of POA. Fourier Transform infra-red (FT-IR) and UV-vis spectral analyses reveal the existence of hydrogen bonding interactions between the groups in PET and POA. X-Ray diffraction analysis informs that the amorphous characteristic of PET is affected by the presence of POA in the composite. UV-vis spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Because oCVD naturally confines the polymerization process to be at the surface where PANI is being deposited, it is reasonable to believe that PANI would have a dominating impact on the observed oCVD reaction kinetics. Furthermore, the literature has suggested that the autocatalytic mechanism could be because of a rapid electron transfer specifically from cation radicals of PANI oligomers to the monomer . Because our FTIR and SEM results support a large amount of oligomer below 90 °C, and our FTIR and XPS results both evidence a more oxidized pernigraniline-like state below 90 °C, it seems reasonable to conclude that the autocatalysis is aided by highly oxidized, short-chain oligomers in this temperature range that leads to the observed oCVD kinetic behavior.…”
Section: Resultssupporting
confidence: 65%
“…Because oCVD naturally confines the polymerization process to be at the surface where PANI is being deposited, it is reasonable to believe that PANI would have a dominating impact on the observed oCVD reaction kinetics. Furthermore, the literature has suggested that the autocatalytic mechanism could be because of a rapid electron transfer specifically from cation radicals of PANI oligomers to the monomer . Because our FTIR and SEM results support a large amount of oligomer below 90 °C, and our FTIR and XPS results both evidence a more oxidized pernigraniline-like state below 90 °C, it seems reasonable to conclude that the autocatalysis is aided by highly oxidized, short-chain oligomers in this temperature range that leads to the observed oCVD kinetic behavior.…”
Section: Resultssupporting
confidence: 65%
“…In the second step, while the composite exhibited a weight loss of 5.9% between 124 and 276 C, a weight loss of 13.7% was observed between 113 and 330 C in the POA, which can be attributed to the loss of the dopant from the POA chains [34]. In the last step, major weight losses occurred in the composite as a result of the structural decompositions of the POA and PET chains [35]. These weight losses (57.2%) were lower than that of PET nonwoven (78.1%) sample between 390 and 500 C. On the other hand, it was observed that the degradation temperature of PET (398 C) slightly decreased to 391 C after the incorporation of POA to its structure.…”
Section: Tgamentioning
confidence: 96%